K.K. Platonov and the system of concepts of Soviet psychology - N.A. Vlasov; V.A. Mazilov (Культурно-историческая психология, 2025)
Context and relevance. In recent years, there has been an increased interest among members of the scientific community in the problem of the conceptual space of psychological science, which makes the analysis of past research experiences of this kind especially relevant. Objective of the study was to identify the ideas of the scientist K.K. Platonov about the system of concepts of psychological science in connection with the philosophical and methodological context of its development in the 70s—80s of the last century. Hypothesis. K.K. Platonov developed the problem of the conceptual space of Soviet psychology and proposed a system of concepts, taking into account the philosophical and methodological features of its development at that time. Methods and materials. Comparative historical and bibliographic methods, categorical analysis were applied in the course of the research; the monographic publications of K.K. Platonov devoted to the problem of concepts of psychological science formed the source base of the research. Results. In the course of the research, comparative historical and bibliographic methods and categorical analysis were applied. The research examines the scientist's views on the general state of the conceptual space of psychology in the Soviet Union and shows the reasons why he decided to address this topic — the lack of proper attention from specialists to the problem of concepts, the uncertainty of the meanings of even basic concepts, and the lack of attempts to build a system of them. In the course of the study, K.K. Platonov's system of concepts in psychology was analyzed, revealing its constituent general philosophical, general psychological, and private psychological categories and the links between them. The direct influence of reflection theory and systems theory on the scientist's conceptual constructions is shown; explanations for this phenomenon are provided. The systems of psychological concepts of K.K. Platonov and B.F. Lomov are compared; their similarities and differences are highlighted and explained. Conclusion. K.K. Platonov became one of the first Soviet scientists to pose the problem of the concepts of psychological science. He carried out its in-depth methodological analysis and proposed a related and internally consistent categorical system, the fundamental importance of which remains to this day.